2011
DOI: 10.1016/j.urology.2010.06.064
|View full text |Cite
|
Sign up to set email alerts
|

Tandem-robot Assisted Laparoscopic Radical Prostatectomy to Improve the Neurovascular Bundle Visualization: A Feasibility Study

Abstract: INTRODUCTION-The preservation of the neurovascular bundle (NVB) during radical prostatectomy improves the postoperative recovery of sexual potency. The accompanying blood vessels in the NVB can serve as a macroscopic landmark to localize the microscopic cavernous nerves in the NVB. We examined the feasibility of image-guided navigation using transrectal ultrasound (TRUS) to visualize NVB during robot assisted laparoscopic radical prostatectomy (RALP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 21 publications
0
27
0
1
Order By: Relevance
“…Three approaches to robotic TRUS-guided RALP have been investigated. The first system, proposed by Han and colleagues, 59 enables the surgeon to view a 3D reconstruction of the prostate gland on a screen separate from the console view, aiding intra operative planning. Secondly, Hung et al 60 demonstrated the use of a ViKY® robotic TRUS-manipulated system (EndoControl® Medical, Grenoble, France) in which the ultrasound scan was able to identify biopsy-proven capsule-abuttin g lesions in 50% of patients (n = 10).…”
Section: Prostatectomy and Lymph Node Dissectionmentioning
confidence: 99%
“…Three approaches to robotic TRUS-guided RALP have been investigated. The first system, proposed by Han and colleagues, 59 enables the surgeon to view a 3D reconstruction of the prostate gland on a screen separate from the console view, aiding intra operative planning. Secondly, Hung et al 60 demonstrated the use of a ViKY® robotic TRUS-manipulated system (EndoControl® Medical, Grenoble, France) in which the ultrasound scan was able to identify biopsy-proven capsule-abuttin g lesions in 50% of patients (n = 10).…”
Section: Prostatectomy and Lymph Node Dissectionmentioning
confidence: 99%
“…The outline of the kidney can be approximately delineated in the elastogram, as well as the contrasting internal collecting system. In addition to the use with kidneys, studies have shown that B-mode and strain imaging are useful for prostatectomy [6], and the system described in this paper could easily be applied to this procedure. The surgeon would also have the option to combine information from a trans-rectal ultrasound transducer and the da Vinci controlled transducer.…”
Section: In Vivo Feasibilitymentioning
confidence: 99%
“…Similarly, the capacity of intraoperative transrectal ultrasound to visualize functionally important structures, such as the urinary sphincter or the neurovascular bundles, has been demonstrated and the interest of including such images in the laparoscopy images is becoming clear. Among the several conceivable approaches is the one described in [20], which proposes pairing a specific robot to hold the endorectal catheter with a DaVinci ® system. Further development of this type of approach is certain; it will be facilitated or demanded by the appearance of new miniaturized ultrasound sensors that can be used, for example, in arthroscopic procedures [21], or by the widespread use of new ultrasound imaging modalities, such as elastography.…”
Section: Improvement In Perceptionmentioning
confidence: 99%